The happy and hopeful NCAA Division I athlete: Predicting well-being and ill-being in elite student-athletes who participate in sport - Chang, E. C. (Research Quarterly for Exercise and Sport, 2025)
The role of hope and happiness in accounting for mental health, both well-being (viz. life satisfaction & flourishing) and ill-being (depressive symptoms & suicidal ideation), using a cross-sectional design, was examined in a diverse sample of 140 elite student-athletes (88 female & 52 male NCAA Division I athletes, representing 16 different varsity sports, Mage = 20.0) who completed a battery of self-report measures. Results from conducting a series of hierarchical regression analyses, controlling for demographic factors and perceived sport performance (individual & team), indicated hope and happiness (as a positive personality set) accounted for additional unique variance in all indices of well-being and ill-being. However, although happiness emerged as a significant statistical predictor of all indices of well-being and ill-being, hope only emerged as a significant statistical predictor across indices of well-being. Importantly, the inclusion of the Hope × Happiness interaction term consistently added further incremental validity to the prediction of additional unique variance in all indices of mental health in student-athletes. However, evidence for the doubling-up hypothesis was only found in predicting indices of well-being, not ill-being. Taken together, the present findings provide strong evidence for the importance of integrating positive individual differences variables for understanding mental health in elite student-athletes.